Comparative Study Aerodynamics Effects of Wingtip Fence Winglet on Fix Wing Airfoil Eppler E562 - Setyo Hariyadi Suranto Putro; Sutardi Sutardi; Wawan Aries Widodo; Bambang Juni Pitoyo (Research and Development Agency of The Ministry of Transportation, 2019)
Wings on airplanes and Unmanned Aerial Vehicles (UAVs) have a very important role in the formation of lift forces. This is because most of the lifting force arises on the wing. Therefore, aircraft designers pay great attention to wing modification. Today's aircraft designers tend to provide geometric modifications displayed in computational applications so that visualization of fluid flow can appear clearly. By increasing the lift as high as possible on the wing and lowering the drag as low as possible, it is expected that high aerodynamic efficiency will be achieved in air transportation. This research was done numerically by using the turbulence model k-ω SST. Reynolds number in this research was 2,34 x 104 with the angle of attacks are 0o, 2o, 4o, 6o, 8o, 10o, 12o, 15o, 17o and 19o. The model specimen is wing airfoil Eppler 562 with winglets. Two types of wingtips are used: forward and rearward wingtip fence. From this study, it was found that the wingtip fence reduced the strength of vorticity magnitude on the x-axis and z-axis compared to plain wings. With the addition of a wingtip fence, it has a significant effect on the shape of the vorticity magnitude behind the wing. This indicates a decrease in induced drag on the wing which has a wingtip fence.